Expression and functional characterization of the BNIP3 Protein in renal cell carcinomas - Macher-Göppinger, Stephan; Keith, Martina; Hatiboglu, Gencay; Hohenfellner, Markus; Schirmacher, Peter; Roth, Wilfried; Tagscherer, Katrin (Translational oncology, 2017)
BNIP3 (Bcl-2/adenovirus E1B 19-kDa interacting protein 3) is a BH3-only protein that regulates apoptosis and autophagy. BNIP3 plays also an important role in hypoxia-induced cell response and is regulated by HIF1. Here, we studied a possible association of BNIP3 expression and the prognosis of patients with renal cell carcinomas (RCCs) and examined the functional relevance of BNIP3 in the regulation of cell survival and apoptosis of renal carcinoma cells. BNIP3 expression was determined by immunohistochemistry in RCC tumor tissue samples of 569 patients using a tissue microarray. Functional characterization of BNIP3 in renal carcinoma cells indicates prosurvival effects. In human RCC tumor samples, high cytoplasmic BNIP3 expression was associated with high-grade RCCs and regional lymph node metastasis. BNIP3 expression correlated negatively with disease-specific survival. Multivariate Cox regression analysis retained BNIP3 expression as an independent prognostic factor in patients without distant metastasis. Together, our studies imply that BNIP3 regulates cell survival in RCCs and its expression is an independent prognostic marker in patients with localized RCCs.
Gesehen am 23.07.2018